2001
DOI: 10.2113/gsrocky.36.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Origin and emplacement of igneous rocks in the central Wasatch Mountains, Utah

Abstract: The calc-alkaline igneous rocks in the central Wasatch Mountains were emplaced between 36-30 Ma. They form a belt comprised of eleven stocks and the Keetley volcanic field aligned along the crustal suture between the Archean Wyoming province and accreted Paleoproterozoic terranes. Magmatism associated with this belt and its westward continuation into the Bingham mining district has been related to midCenozoic extension. These rocks consist of two types of stocks based on texture: a western type, which is coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 51 publications
1
28
1
Order By: Relevance
“…During the Early Eocene and early Middle Eocene, the Absaroka and Challis Volcanic Fields were emplaced in the northern Cordillera. However, the 87 Sr/ 86 Sr ratios of Tertiary volcanics in the North American Cordillera nowhere exceed 0.709 (Peterman et al, 1970;Meen, 1987;Cunningham et al, 1998;Dostal et al, 2001;Vogel et al, 2001) Sr ratios observed in Lake Gosiute , which would require an increase in windblown carbonate to that lake. This seems implausible.…”
Section: Evidence For Drainage Reorganizationmentioning
confidence: 94%
“…During the Early Eocene and early Middle Eocene, the Absaroka and Challis Volcanic Fields were emplaced in the northern Cordillera. However, the 87 Sr/ 86 Sr ratios of Tertiary volcanics in the North American Cordillera nowhere exceed 0.709 (Peterman et al, 1970;Meen, 1987;Cunningham et al, 1998;Dostal et al, 2001;Vogel et al, 2001) Sr ratios observed in Lake Gosiute , which would require an increase in windblown carbonate to that lake. This seems implausible.…”
Section: Evidence For Drainage Reorganizationmentioning
confidence: 94%
“…Apparently several magma systems were episodically active beneath the Carlin trend during the Eocene and Oligocene (Grauch et al, 2003;Ressel and Henry, 2006). Concurrent magmatism occurred at similar latitudes in Utah, including that responsible for the Bingham, Clayton, and Alta stocks (Vogel et al, 2001;Deino and Keith, 1997).…”
Section: Geotectonic Settingmentioning
confidence: 99%
“…Zircon U/Pb ages for the intrusions range from 36 Ma for the Clayton Peak stock to 30 Ma for the western Little Cottonwood stock [ Feher et al , 1996; Constenius , 1998]. The easternmost intrusions are porphyritic with microcrystalline to fine‐grained groundmass and include the Flagstaff, Ontario, Mayflower, and Pine Creek stocks, which range in age from ∼34 to ∼39 Ma [ Vogel et al , 1997; Constenius , 1998, and references therein]. The Keetley Volcanics crop out east of the easternmost intrusions dated in this study.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…In Figure 2b, sample numbers are keyed to Tables 1 and 2. In Figure 2c, numbers in parentheses and brackets are intrusion age and depth ranges [ John , 1989; Feher et al , 1996; Vogel et al , 1997; Constenius , 1998]. LCC, Little Cottonwood Canyon; BCC, Big Cottonwood Canyon; LCS, Little Cottonwood Stock; AS, Alta Stock; CPS, Clayton Peak Stock; OFMS, Ontario, Flagstaff, and Mayflower stocks; PPS, Park Premier stock; SF, Superior Fault; SFF, Silver Fork Fault; AGT, Alta‐Grizzly Thrust; AFF, American Fork Fault; DCF, Deer Creek Fault; CNT, Charleston‐Nebo Thrust.…”
Section: Introductionmentioning
confidence: 99%